Optimalisasi Kepemimpinan Kepala Sekolah dalam Meningkatkan Prestasi Olahraga (Studi Kasus Siswa SDN Sindangjaya dalam Perspektif Pendidikan Karakter) - H. Soro, Suharyanto; Suherman, Maman; Taryana, Iwan; Kustamaji, Erwin; Itang, Itang (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
This study explores the school principal leadership to increase the sport achievements of students at SDN Sindangjaya, focusing on how this leadership approach affects towards development of sports programs and student engagement. The method used is qualitative. Data were obtained in the field through observation, structured interviews, and documentation. The samples from this research were school principal, teachers, students. They were taken by purposive sampling. Next stage involves interpreting the data to generate information or knowledge. The research findings indicated that school principal leadership at SDN Sindangjaya plays a crucial role in increasing students' sports achievements. This approach recognizes and involves every teacher and student in sports decision-making, encourages their active participation and contribution, and facilitates the development of innovative training methods and teacher professionalism. However, the optimalisation of this school principal leadership faces obstacles, including limited resources and sports facilities, resistance to change from some teachers, and challenges in balancing the needs and desires of various students.